Antihyperglycemic and Antihyperlipidemic Effects of Lippia citriodora in Rats - El-Ouady, Fadwa; Eddouks, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Aim: The study was conducted to assess the antidiabetic and antihyperlipidemic effects of Lippia citriodora. Background: Lippia citriodora Kunth (Verbenaceae) is a medicinal plant with many traditional uses. Objective: The goal of this study was to investigate the antidiabetic activity of aqueous extract of Lippia citriodora and its capacity to improve the lipid profile in diabetic rats. Methods: Normal and diabetic rats were treated orally for 15 days by the leaves aqueous extract of Lippia citriodora (LCLAE) (100 mg/kg). The whole glucose utilization and liver architecture were also evaluated. The in vitro antioxidant activity of LCLAE was also assessed. Results: LCLAE lowered blood glucose and lipid levels in all groups. Moreover, LCLAE ameliorated the liver structure and exhibited antioxidant activity. Conclusion: In conclusion, this study demonstrates the hypoglycemic and antihyperlipidemic effects of LCLAE in rats.
Keywords: antioxidant activity